Technology and spirituality in Etsuko Ichihara's ludic media art. Issue 3 (2nd September 2022) - Sone, Yuji
ABSTRACT: Etsuko Ichihara is a media artist who utilises digital media and robotic technologies, exploring Japanese traditional beliefs of the spirit and the supernatural in her recent works. Ichihara repurposes paranormal and folk religious ideas concerning the figure of the shaman, an ogre-like demon that features in some Japanese festivals, and ritual offerings, but reinvents these traditional elements through technological mediation. I discuss Ichihara's distinctive engagement with a contemporised notion of spirituality in Japan. In particular, this essay argues that Ichihara's media art aims to connect Japanese people in order to create sociality and community. Ichihara appropriates Japanese animistic beliefs and tailors them for a mediated and technologised Japan, utilising what might be called a 'techno-spiritual Japanese-ness', that is, self-orientalising tropes that paradoxically generate the means for social relations.